Differential gene expression profile in Porphyromonas gingivalis treated human gingival keratinocytes and their role in the development of HNSCC - Dakshinya M; Anitha P; A.S. Smiline Girija; Paramasivam A; Vijayashree Priyadharsini J (Journal of Oral Biology and Craniofacial Research)
Background: Periodontitis is considered to be one of the major risk factors associated with cancers of the oral cavity. Periodontogenic pathogens such as Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans are the important pathogens associated with periodontitis. Chronic exposure to bacterial components induces changes in the nearby cells. Hence, the present study has been designed to identify the molecular mechanisms that could be associated with the two disease conditions viz., periodontitis and head and neck cancer. Objective: The present study investigated the differential gene expression profile in human gingival keratinocytes treated with P. gingivalis (Pg), a bacterium associated with periodontal disease, and its possible association with the development of Head and Neck Squamous Cell Carcinoma (HNSCC). Methods: The study followed a computational design. Multiple tools and databases, such as GEOmnibus, STRING, Metascape, PANTHER, and UALCAN, cBioportal, were used to derive an association between gene expression during infection with P. gingivalis, and the resulting gene expression profiles were analyzed in the HNSCC dataset. Results: The study revealed 29 genes from a pool of transcripts acquired after comparing the Pg-HIGK and Sham-HIGK. Among them, 3 genes i.e., FST, VRK3, and SGK1, were found to be overexpressed and significantly influenced patient survival. The upregulation of FST was found to correlate with poor prognosis in HNSCC patients. Conclusion: The study provided insights into the possible association of FST, VRK3 and SGK1 in the development of HNSCC. Further investigations are warranted to confirm the functional role of these genes in establishing the cancer phenotype in patients with chronic infection with Pg.